MEMBANGUN KARAKTER DALAM PERSPEKTIF FILSAFAT PENDIDIKAN - Alamin Alamin; Muhammad Nurwahidin; Sudjarwo Sudjarwo (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
Forming character in the world of education is an initial effort that is structured and programmed to train and develop students' abilities in instilling and familiarizing commendable behavior. This research technique uses a Literature Review study. References for this writing come from journals, papers, and articles from 2018 to 2022. The results of this experiment are: 1). The development of character education in Indonesia has started since the preschool age 0-6 years and the school age 6-13 years through the development of the K.13 Curriculum by developing the goals of core competencies, namely the competence of spiritual attitudes, social attitudes, knowledge, and skills. 2). Creating a student's personality must instill three keys to education, namely parents, the world of education, and the public. 3). In applying the philosophy of education in schools, teachers should strengthen morals to students, as taught by the figures of Indonesian Education philosophy, namely "Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, Tut Wuri Handayani". That is, a leader must be able to position himself as a role model or example, a balancer, and as a motivator.